Odpowiedzi

  • Użytkownik Zadane
2013-07-14T19:21:58+02:00

5/6 + 1 2/3= 5/6 + 1 i 4/6 = 1 i 9/6 = 1 i 3/2 = 2 i 1/2


1-1/2 x 1/3= 1 - 1/6 = 6/6 - 1/6 = 5/6

2013-07-14T19:22:45+02:00

\frac{5}{6} + 1 \frac{2}{3} = \frac{5}{6} + \frac{5}{3} = \frac{5}{6} + \frac{10}{6} = \frac{15}{6} = 2 \frac{3}{6} = 2 \frac{1}{2} \\ \\ 1 - \frac{1}{2} \cdot \frac{1}{3} = 1 - \frac{1}{6} = \frac{6}{6} - \frac{1}{6} = \frac{5}{6}

 

----------------------------------------------------------------------------------------------------

Litterarum radices amarae sunt, fructus iucundiores

 

Pozdrawiam :)